Crambe dry matter and yield under doses of phosphorus and base saturation in the Cerrado of Goiás - José M. Alves; Wilson M. Leandro; Cassia C. F. Alves; Leandro Carlos; Adriana A. Ribon; Kathleen L. Fernandes (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Crambe has been studied as an option in crop rotation systems in order to provide raw material for biodiesel production. This study aimed to evaluate the effect of raising soil base saturation and addition of phosphorus (P) on the vegetative development, grain yield and oil content of crambe. The experiment was carried out in a Oxisol, arranged in factorial scheme (4 x 3), with 4 replicates (48 plots), in completely randomized blocks. Four base saturation levels (34 - natural of the soil, 40, 50 and 60%) and three P doses (0, 40 and 80 kg ha-1 of P2O5) were evaluated. The experimental plots formed a 9 m2 rectangle with 5 plant rows, spaced by 0.45 m, using the cultivar "Brilliant FMS". The evaluated variables were: dry matter of roots and shoots at three different times (35, 45 and 55 days after emergence), grain yield and oil content. Base saturation favored crambe root and shoot development, yield and oil content, with the best results for base saturation of 47-48%. The addition of P doses also favored the increase of the analyzed variables.